Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 29 (1986) (Human Rights and Humanitarian Law - Book Archive pre-2000., 1991)
This volume of the Yearbook of the European Convention on Human Rights , prepared by the Directorate of Human Rights of the Council of Europe, relates to 1986. Its presentation follows that of the previous volume. Part one contains basic texts and information of a general nature; part two deals with the European Commission of Human Rights; part three with the European Court of Human Rights; part four with the Resolutions of the Committee of Ministers; and parts five and six with the other work of the Council of Europe in the field of human rights, the situation in the Member States and developments within the European Communities. A Bibliography and Index are included. Ce volume de l'Annuaire de la Convention européenne des Droits de l'Homme, préparé par la Direction des Droits de l'Homme du Conseil de l'Europe, concerne l'année 1986. La première partie contient des textes fondamentaux et des informations de caractère général; la deuxième partie contient les rapports de la Commission européenne des Droits de l'Homme; la troisième partie donne des informations sur la Cour européenne des Droits de l'Homme; la quatrième partie contient les Résolutions du Comité des Ministres; et les cinquième et sixième parties regroupent toutes les autres activités concernant la Convention dans le cadre du Conseil de l'Europe et comprennent des informations sur les débats devant les parlements nationaux et sur les développements au sein des Communautés européennes concernant la protection des droits de l'homme. Le volume se termine avec une bibliographie et un index alphabétique.